SULFIDE MINERAL SURFACES - Rosso K.M.; Vaughan D.J. (My University, 2006)
The past twenty years or so have seen dramatic development of the experimental and theoretical tools available to study the surfaces of solids at the molecular (?atomic resolution?) scale. On the experimental side, two areas of development well illustrate these advances. The first concerns the high intensity photon sources associated with synchrotron radiation; these have both greatly improved the surface sensitivity and spatial resolution of already established surface spectroscopic and diffraction methods, and enabled the development of new methods for studying surfaces. The second centers on the scanning probe microscopy (SPM) techniques initially developed in the 1980's with the first scanning tunneling microscope (STM) and atomic force microscope (AFM) experiments. The direct 'observation' of individual atoms at surfaces made possible with these methods has truly revolutionized surface science. On the theoretical side, the availability of high performance computers coupled with advances in computational modeling has provided powerful new tools to complement the advances in experiment. Particularly important have been the quantum mechanics based computational approaches such as density functional theory (DFT), which can now be easily used to calculate the equilibrium crystal structures of solids and surfaces from first principles, and to provide insights into their electronic structure. In this chapter, we review current knowledge of sulfide mineral surfaces, beginning with an overview of the principles relevant to the study of the surfaces of all crystalline solids. This includes the thermodynamics of surfaces, the atomic structure of surfaces (surface crystallography and structural ...